Redefining pedestrian accessibility through inclusive design and community engagement - Dewi Junita Koesoemawati; Akhmad Hasanuddin; Fidyasari Kusuma Putri; Teguh Hadi Priyono; Sebastiana Viphindrartin (Urbani Izziv, 2025)

(untitled)
In many developing regions, inclusive pedestrian infrastructure remains insufficient to support the mobility and autonomy of individuals with disabilities. This study focuses on Jember Regency, Indonesia, where accessibility barriers such as narrow pavements, broken surfaces, and the absence of multisensory navigation tools persist. Employing a qualitative exploratory approach, the study integrates online questionnaires, focus groups, site inspections, and a literature-based benchmarking process. These mixed tools were used to identify real-world user challenges and validate local design preferences against global accessibility standards. The findings reveal two major categories of accessibility barriers: physical and structural, as well as emotional and psychosocial barriers. The results emphasize the need for context-sensitive, multisensory infrastructure features, including braille signage, audible indicators, and tactile paving. The study presents design recommendations that align global best practices with local anthropometric and cultural contexts through a glocalized framework. By embedding user voices in the design process and adapting international principles to regional realities, this research contributes both methodologically and conceptually to discourse on inclusive urban design, particularly within underrepresented contexts of the Global South.